Small Surface Fatigue Crack Behaviors of Cr-Mo Steel AISI4137 - Seung-Hoon Nahm; Sang-Koo Jeon; Dong-Kyun Kim; Min-Soo Suh; Chang-Min Suh (Crystals)
Costs are increasing due to the addition of alloying elements such as V, W, and Mo to prevent damage to Cr-Mo steel for fastening bolts, but field tests have shown that it is not an appropriate solution for improving physical properties through heat treatment. In this study, the characteristics of fatigue cracks using Cr-Mo steel for fastening bolts before and after UNSM (ultrasonic nanocrystal surface modification) treatment were studied using fracture mechanics and fracture analysis methods. Specifically, using untreated and UNSM-treated materials: (1) the characteristics of small surface fatigue cracks existing on the surface, and (2) the surface fatigue cracks in the depth direction were observed and analyzed. The microstructure of Cr-Mo steel was refined by severe plastic deformation (SPD) from the surface to a depth of about 100 μm according to the static load of UNSM, and the fatigue limit increased by 30% as a large compressive residual stress was formed. Additionally, like the untreated materials, fisheye cracks did not occur in UNSM-treated materials, even when inclusions were present, and all specimens fractured while forming surface cracks. Accordingly, one or more of the multiple small surface fatigue cracks (MSFC) grew and developed into a major crack that determines the fatigue life, and a major ridge was formed among the many micro-ridges in the internal direction. In other words, this major crack grew and developed a major ridge in the internal direction, determining the lifespan of the test specimen.